Despre fizica născută la Iași: Ștefan Procopiu (1890-1972). - OLARIU, Ivona (Quaestiones Romanicae, 2025)
The Physics and Chemistry Library, a specialized library, branch of "Mihai Eminescu" Central University Library in Iași, is named after Ștefan Procopiu (1890-1972), paying tribute to his outstanding contributions to the development of Physics all over the world. It is keeping, within its collections, the personal archive donated to the Library by Mrs. Rodica Procopiu. This paper, the first in a series dedicated to presenting the Procopiu archive, analyzes aspects of his professional career: achievements of the research work (over 170 papers), whose results were predictable due to evident scientific interests since high school, continued as a student at the Faculty of Physical and Chemical Sciences, and developed during the doctoral program supervised by professors G. Lippmann and A. Cotton in Paris; his role in developing Physics at the University of Iași, where he was a professor from 1925 to 1962; other aspects related to his life and career. All these aspects are supported by documents from the donation files (diplomas, excerpts, correspondence, research result sheets, postcards). The paper also includes the presentation of some books from the library's collections written by Procopiu, such as "Sur la birefringence electrique et magnetique de suspensions," published in 1924 by Mason Publishing House, "Electricity and magnetism," a course taught at the Faculty of Sciences in Iași and at "Gh. Asachi" Polytechnic Institute, edited between 1939-1942, or the university course on Thermodynamics from 1948. His activity not only marked the development of physics but also fulfilled the mission of the university to spread science, but also to create values itself.